Correlation between peak ground acceleration and strength parameters of residual soil - Baharudin, N. H. (Research India Publications, 2016)
The purpose of this study was to find the correlation between the value of Peak Ground Acceleration (PGA) and the strength parameters of residual soil; cohesion and friction angles. The value of PGA chosen was 50, 100, 200, 500, 700 and 950 gals respectively. The compacted soil samples were put on the Shaking Table and experienced the Peak Ground Acceleration of different intensity as mentioned above for the duration of 21 seconds and 12 seconds. These samples were then tested for Unconsolidated Undrained (UU) Triaxial Test following the procedures in BS 1377: Part 6:1990. Results of the experiment showed the significant correlation between the various values of Peak Ground Acceleration (PGA) and the cohesiveness and friction angles of the residual soil tested. Increasing duration of PGA would increase the value of cohesiveness and decrease the value of friction angle of the soil whereas increasing intensity of PGA would result in the decrease in cohesiveness and the increase in friction angles. The study also showed that the values of cohesiveness for the soil in static loading condition which was not exposed to PGA turned out to be lower than the values of cohesiveness for the soil that were exposed to PGA with all intensities tested. On other hand, the value of friction angles for the soil under static loading condition was found to be lower than the value of friction angles under seismic loading condition with all PGA intensities tested.